Red : the true story of Red Riding Hood - Shurtliff, Liesl (Alfred A. Knopf, 2016)
"Followed by a wolf, a huntsman, and a porridge-sampling nuisance called Goldie, Red embarks on a quest to find a magical cure for her ailing grandmother"--